Oil palm inflorescence sex ratio and fruit set assessment in dura × pisifera biparental progenies on fibric peat soil - Swaray, Senesie; Amiruddin, Mohd Din; Y., Mohd Rafii; Jamian, Syari; Ismail, Mohd Firdaus; Jalloh, Momodu; Eswa, Mazli; Marjuni, Marhalil; Akos, Ibrahim Silas; Yusuff, Oladosu (MDPI, 2021)
This study investigated oil palm inflorescence sex ratio (ISR) and fruit set (FS) yield among 24 dura × pisifera biparental progenies on fibric peat soil, hybridized from ten genetic origins. Three-month intervals of data collection on ISR and “S-shape” procedure for FS determination were carried out in an independent complete randomized design for one year. Based on the assessment of individual progenies, analysis of variance revealed the existence of genetic heterogeneity. Five of the progenies had the highest ISR above 90%. However, 20.83% of the progenies (PK4841, PK4674, ECPHP415, ECPHP550, and PK4118) had the best normal range of ISR, indicating FS declined being influenced by ISR. Therefore, only 12.50% of the progenies (PK4674, PK4465, and PK4482) were above 60% FS critical level. Correlation analysis verified that ISR depends on the female flower and progeny PK4674 (65.78%) and PK4465 (62.62%) had the best FS and fruit to bunch. Among the parental origins, Deli Serdang × Cameroon was statistically the best for male flower production at 29.40% and ISR at 72.22%. The highest FS was recorded in Deli Banting × AVROS (54.00%) and Angola × AVROS (53.78%). However, molecular research, such as microsatellite molecular markers if concurrently used as a selection criterion with the present conventional study, could present further details to complement the present findings.